Effect of cardiac rehabilitation on 24-month all-cause hospital readmissions: A prospective cohort study. (March 2019) - Thomas, Emma; Lotfaliany, Mojtaba; Grace, Sherry L; Oldenburg, Brian; Taylor, C Barr; Hare, David L; Rangani, WP Thanuja; Dheerasinghe, DS Anoja F; Cadilhac, Dominique A; O'Neil, Adrienne
Background: Ageing populations and increasing survival following acute coronary syndrome has resulted in large numbers of people living with cardiovascular disease and at high risk of hospitalizations. Rising hospital admissions have a significant financial cost to the healthcare system. Aim: The purpose of this study was to determine whether cardiac rehabilitation is protective against long-term hospital readmission (frequency and length) following acute coronary syndrome. Methods: Data from 416 Australian patients with acute coronary syndrome enrolled in the Anxiety Depression and heart rate Variability in cardiac patients: Evaluating the impact of Negative emotions on functioning after Twenty four months (ADVENT) prospective cohort study between January 2013–June 2014 was analyzed secondarily. Participants self-reported cardiac rehabilitation attendance over the 12 months post-discharge. All-cause readmission data were extracted from hospital records 24 months post-index event. The association between cardiac rehabilitation and all-cause readmission, frequency of readmissions, and length of stay was assessed using three methods (a) regression analysis, (b) propensity score matching, and (c) inverse probability treatment weighting. Results: Overall, 416 patients consented (53% of eligible patients), of which 414 (99.5%) survived the first 30 days post-discharge and were included in the analysis. Medical records were located for 409 participants after 24 months (98% follow-up rate). In total, 267 (65%) reported attending cardiac rehabilitation; there were 392 readmissions by 239 patients. Cardiac rehabilitation attendance was not associated with all-cause hospital readmission; however, it was associated with lower frequency of hospital admissions ( odds ratio 0.53, 95% confidence interval: 0.31–0.91 p-value:0.022) and length of stay (coefficient –1.21 days, 95% confidence interval: –2.46–0.26; marginally significant p -value: 0.055) in adjusted models. Conclusion: This study substantiates the long-term benefits of cardiac rehabilitation on readmissions, including length of stay, which would result in lower costs to the healthcare system.